2020
DOI: 10.1021/acsapm.0c01087
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Brush Functionalization of Polyurethane Tunable Nanopores for Resistive Pulse Sensing

Abstract: Nanoscale control over pore surface properties is a challenging objective for nanopore research and could enable advanced bioanalytical applications, along with enhanced precision and accuracy of existing measurement processes. This work reports a one-pot strategy for the functionalization of thermoplastic polyurethane (TPU) tunable nanopores with polymer brushes. These elastomeric pores are used for tunable resistive pulse sensing (TRPS), which can detect and analyze a broad range of microparticle and nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 101 publications
0
11
0
Order By: Relevance
“…One extensively used approach for such functionalization of nanochannels and nanopores has been grafting charged and environmental-stimuli−responsive polyelectrolyte (PE) brush molecules on the inner walls of the nanochannel/nanopores. The responsiveness of these brush molecules to environmental stimuli makes them behave differently under different environmental conditions, which in turn enable the use of such brush-functionalized nanochannels for applications such as biosensing and chemicalsensing, 16 measuring chemical content of biological cells, 17 current rectification, 18 nanofluidic diode fabrication, 19 resistive pulse durations, 20 probing tracer dynamics (through responsive polymeric brush layer or hairy layers grafted on the walls of nanochannels or nanopores) for better understanding particle diffusion in crowded media, 21,22 and many more. Behavior of the PE brushes have been extensively explored over the past several decades using experimental, theoretical, and simulation studies.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One extensively used approach for such functionalization of nanochannels and nanopores has been grafting charged and environmental-stimuli−responsive polyelectrolyte (PE) brush molecules on the inner walls of the nanochannel/nanopores. The responsiveness of these brush molecules to environmental stimuli makes them behave differently under different environmental conditions, which in turn enable the use of such brush-functionalized nanochannels for applications such as biosensing and chemicalsensing, 16 measuring chemical content of biological cells, 17 current rectification, 18 nanofluidic diode fabrication, 19 resistive pulse durations, 20 probing tracer dynamics (through responsive polymeric brush layer or hairy layers grafted on the walls of nanochannels or nanopores) for better understanding particle diffusion in crowded media, 21,22 and many more. Behavior of the PE brushes have been extensively explored over the past several decades using experimental, theoretical, and simulation studies.…”
Section: ■ Introductionmentioning
confidence: 99%
“…We made some of the first attempts to explore in detail the properties and behavior of such PE-brush-supported counterions and water molecules by employing all-atom molecular dynamics simulations for studying the PE brushes. Another critical aspect of PE brush-grafted systems that have been less investigated from the context of fundamental exploration is the manner in which the PE brushes and the brush-supported counterions and water molecules get affected when the brushes are nanoconfined, that is, grafted on the inner walls of a nanochannel. Such a gap is rather surprising given the significant use of PE-brush-grafted nanochannels and nanopores in a variety of applications. Like the all-atom MD simulation-based exploration of PE brushes and brush-supported counterions and water molecules, here too, we established one of the first all-atom MD simulation model to quantify in detail the effect of nanoconfinement on the behavior of PE brushes and the distribution profiles of the brush-supported counterions and water molecules . We identified that for the case of nanoconfined polyacrylic acid (PAA) brushes, screened by Na + counterions in the presence of an additional 0.1 M of NaCl salt, there occurs a most remarkable overscreening (OS) of the PE brush layer caused by the presence of a higher number of counterions within the brush layer than needed to screen the brush charges (such OS, also sometimes referred to as charge inversion effect, has been previously reported for bare nanofluidic or nanoparticle systems containing counterions, but never for PE-brush-grafted nanochannels).…”
Section: Introductionmentioning
confidence: 99%
“…Functionalization of pore surfaces has been emphasized along with the development of RPS, and various functions, such as rectification, can be introduced to the pores. The materials of the pores used for functionalization are also diverse, including semiconductors, glass, and various kinds of polymer membranes. , …”
Section: Introductionmentioning
confidence: 99%
“…Based on the above reasons, an investigation of pore functionalization can enhance the value of RPS. , One problem is the fabrication process of a biosensing surface on a pore because the surface modification is restricted by the base material of the pore surface. In previous reports, pores were prepared in a variety of materials, such as quartz, semiconductors, and polymers, making it difficult to simplify the surface modification process.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advancements in manufacturing and polymer synthesis techniques have made it possible to graft polymer chains to the inner walls of artificial nanopores. The use of responsive and switchable polymers allows the functionalized nanochannel to alter its structural morphology in response to external environmental changes and cues. Their morphological changes can be utilized to, for example, control the conduction and endow the nanopore with gating abilities. , The possibility of incorporating responsive functions into confined geometries represents a significant step forward in the development of smart nanochannel systems.…”
Section: Introductionmentioning
confidence: 99%